NIL “Reform” Fails to Address the NCAA’s Biggest Issue - Richard Southall; Mark S Nagel (Journal of Applied Sports Management, 2021)
Do college sport stakeholders have the intellectual and moral courage to abandon the familiar and financially successful, but morally bankrupt and exploitative, collegiate model? The NIL "Reform," which effectively fails to address the NCAA's biggest issue, is explored in this article.
Keywords: Branding; College Sports; Governance; NCAA; Policy; Student Athletes